2018
DOI: 10.5606/tgkdc.dergisi.2018.15016
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation therapy in pregnant women with mechanical heart valve

Abstract: Bu çalışmada, farklı antikolagülan rejimlerinin protez kapak ile ilişkili komplikasyonlar ve feto-maternal mortalite ve morbidite üzerindeki etkileri araştırıldı ve en ideal antikolagülan tedavi rejimi belirlendi. Ça lış ma pla nı: Ocak 1990-Aralık 2015 tarihleri arasında mekanik kalp kapak replasmanı yapılan gebe kadınlarda antikoagülan tedavi rejimleri, retrospektif olarak incelendi. Mekanik kalp kapak replasmanı sonrası 57 hastada 72 gebelik gözden geçirildi ve dört farklı rejim belirlendi ve gebeliğin fark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 22 publications
(21 reference statements)
0
19
0
2
Order By: Relevance
“…After duplicate removal, 247 studies were identified through database search and screened by title and abstract. A total of 37 studies were finally included 1 2 3 5 8 10 12 13 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ( Table 1 ). In 22 of the included studies, data were retrospectively collected, 6 10 12 13 17 18 19 20 21 23 24 25 26 28 32 36 37 38 40 41 42 43 44 whereas 15 studies collected data prospectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After duplicate removal, 247 studies were identified through database search and screened by title and abstract. A total of 37 studies were finally included 1 2 3 5 8 10 12 13 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ( Table 1 ). In 22 of the included studies, data were retrospectively collected, 6 10 12 13 17 18 19 20 21 23 24 25 26 28 32 36 37 38 40 41 42 43 44 whereas 15 studies collected data prospectively.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 37 studies were finally included 1 2 3 5 8 10 12 13 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ( Table 1 ). In 22 of the included studies, data were retrospectively collected, 6 10 12 13 17 18 19 20 21 23 24 25 26 28 32 36 37 38 40 41 42 43 44 whereas 15 studies collected data prospectively. 1 2 3 5 8 22 27 29 30 31 33 34 35 39 None were randomized controlled trials.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations